On the Influence of Rare Earth Dopants on Thermal Transport in Thermoelectric Bi2Te3 Compounds: An Ab Initio Perspective. Issue 2 (2nd January 2019) - Baranovskiy, Andrei; Harush, Mor; Amouyal, Yaron
Abstract: A density functional theory (DFT) study of thermal transport properties of rare earth (RE) doped Bi2 Te3 compounds (RE = Y, La, Eu, Gd, and Lu) is reported. The calculations reveal strong nonmonotonous concentration dependence of the lattice thermal conductivity (κL ) with local minimum in the region of 2–3 at.% dopant concentration for all dopants in the series except Eu. This behavior is associated with the presence of impurity phonon modes in the frequency range of 0–2 THz. The low‐frequency parts of the phonon spectra vary substantially for different divalent and trivalent RE dopants, which results in different phonon scattering events for different dopants. The concentration dependence of κL correlates with both Grüneisen parameter ( γ ) and sound velocity ( v ). This provides us with a simple and powerful predictive tool assessing thermal transport in RE‐doped Bi2 Te3 compounds. Abstract : The density functional theory is a powerful tool for thermal conductivity evaluation . This procedure requires consideration of both Grüneisen parameter and sound velocity. Doping of bismuth telluride with rare earth elements reduce thermal conductivity. Impurity phonon modes appear at frequencies up to 2 THz. The divalent impurities exhibit stronger effects compared to trivalent ones.